OmpA: a pore or not a pore? Simulation and modeling studies. - Bond, P; Faraldo-Gómez, J; Sansom, MS (2002)
The bacterial outer membrane protein OmpA is composed of an N-terminal 171-residue beta-barrel domain (OmpA(171)) that spans the bilayer and a periplasmic, C-terminal domain of unknown structure. OmpA has been suggested to primarily serve a structural role, as no continuous pore through the center of the barrel can be discerned in the crystal structure of OmpA(171). However, several groups have recorded ionic conductances for bilayer-reconstituted OmpA(171). To resolve this apparent paradox we have used molecular dynamics (MD) simulations on OmpA(171) to explore the conformational dynamics of the protein, in particular the possibility of transient formation of a central pore. A total of 19 ns of MD simulations of OmpA(171) have been run, and the results were analyzed in terms of 1) comparative behavior of OmpA(171) in different bilayer and bilayer-mimetic environments, 2) solvation states of OmpA(171), and 3) pore characteristics in different MD simulations. Significant mobility was observed for residues and water molecules within the beta-barrel. A simulation in which putative gate region side chains of the barrel interior were held in a non-native conformation led to an open pore, with a predicted conductance similar to experimental measurements. The OmpA(171) pore has been shown to be somewhat more dynamic than suggested by the crystal structure. A gating mechanism is proposed to explain its documented channel properties, involving a flickering isomerization of Arg138, forming alternate salt bridges with Glu52 (closed state) and Glu128 (open state).